PENGARUH GAME ONLINE TERHADAP PRESTASI BELAJAR REMAJA KOMPLEK KORPRI KABUPATEN KUBURAYA (STUDI KASUS: MOBILE LEGENDS) - Witriana Endah Pangesti; Rizky Ade Safitri; Qudziah Nur Azizah (Yayasan Akrab Pekanbaru, 2019)
Current technological developments especially those related to smart computer technology are growing rapidly. Until the cellphone was originally used to meet communication needs only, now mobile phones can be used to do many things, such as used to find any information that is in the world very easily, playing online games anywhere and so on. Mobile Legend game is very popular not only by teenage boys, but there are also many teenage girls who like to play online games. According to Fendy, now the